Altered Functional Connectivity Between the Cerebellum and the Cortico-Striato-Thalamo-Cortical Circuit in Obsessive-Compulsive Disorder - Zhang, Haisan; Wang, Bi; Li, Kun; Wang, Xiaoyue; Li, Xianrui; Zhu, Jianli; Zhao, Qingjiang; Yang, Yongfeng; Lv, Luxian; Zhang, Meng; Zhang, Hongxing (Frontiers in Psychiatry, 2019)
Background: Altered resting-state functional connectivity of the cerebellum in obsessive-compulsive disorder (OCD) has been previously reported. However, the previous study investigating cerebellar–cerebral functional connectivity relied on a priori–defined seeds from specific networks. In this study, we aimed to explore the connectivity alterations of the cerebellum in OCD under resting-state conditions with a hypothesis-free approach. Methods: Thirty patients with OCD and 26 healthy controls (HCs) underwent functional magnetic resonance imaging (fMRI) scanning at resting state. Regional cerebral function was evaluated by measuring the fraction of amplitude of low-frequency fluctuation (fALFF). Regions with mean fALFF (mfALFF) alterations were used as seeds in seed correlation analysis (SCA). An independent samples t test was used to compare the differences in mfALFF and functional connection (FC) between the two groups. Pearson correlation analysis was performed to identify the association between functional neural correlates and OCD symptom severity evaluated using the Yale-Brown Obsessive Compulsive Scale (Y-BOCS). Results: Compared with the HC group, the OCD group showed significantly increased mfALFF values in bilateral cerebellar. The results of FC analysis showed weakened connectivity among the left Crus II, lobule VIII, and right striatum and between the right lobule VIII and the right striatum, and cingulate in the OCD group compared with the HC group. Some of the abovementioned results were associated with symptom severity. Conclusions: OCD patients showed abnormal spontaneous cerebellar activity and weakened functional connectivity between the cerebellum and the cortico-striato-thalamo-cortical (CSTC) circuit (striatum and cingulate), suggesting that the cerebellum may play an essential role in the pathophysiology of OCD.